The Influence of Internal/Rolling Mutations and Job Satisfaction on Employee Performance in Batam Prime Customs and Excise Office Type B - Awal, Ansari Maulidil; Tarigan, Yulinda (Pusat P2M Politeknik Negeri Batam, 2024)
The objective of this research is to investigate the impact of job rotation on staff performance, the influence of job satisfaction on employee performance, and whether there is a combined influence of job satisfaction and rotation on performance within the Batam Customs and Tax Chief Office Type B. This research employs a quantitative approach utilizing SPSS version 20 and the multiple linear regression analysis method for hypothesis testing. The sampling technique applied in this research is convenience sampling, and the sample size was determined using the Yamane formula. Out of a total population of 368 employees, 192 were selected as respondents for the research. Data collection was conducted through the distribution of questionnaires using Google Forms, as well as through interviews and documentation. According to the research, there is no statistically significant relationship between the rotation variable and employee performance. Staff performance is significantly influenced by job satisfaction. Additionally, both internal mutation/rolling and job satisfaction have an impact on officer performance.